High Frequency of Gram-negative Bacilli (GNB) Pathogens in Wounds and Other Clinical Specimens: A Grave Public Health Concern - Urooj, Seerat ul; Bano, Shaista; Tunio, Sarfraz Ali; Memon, Babar Aijaz; Abbasi, Shah Muhammad; Rajput, Zainab (BioScientific Review, 2024)
Background. Gram-negative bacilli (GNB) including Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii are important causes of both hospital and community acquired infections in human beings. In this regard, the current study aimed to assess the frequency of GNB pathogens circulating in Hyderabad, Sindh and to obtain locally applicable data for the prevention and spread of infections caused by GNBs. Methodology. A total of 360 clinical specimens including blood, pus, wound, urine, sputum, and body fluids from suspected indoor and outdoor patients were collected from various diagnostic centers of Hyderabad, Sindh. The isolation, identification, and characterization of GNB pathogens was performed by using standard conventional methods including morphological, cultural, and biochemical testing. Results. A total of 143 GNBs were isolated and characterized in the current study. The data demonstrated that male patients were more affected with GNBs accounting for 55.94% (n=80) of infected specimens, whereas 44.06% (n=63) of specimens were from female patients. Moreover, specimen wise data of sample positivity revealed that 13.29% (n=19) of GNBs were isolated from pus specimens, 58.59% (n=70) from urine specimens, 34.97% (n=50) from blood specimens, 1.40% (n=2) from fluid specimens, and 1.40% (n=2) of GNBs were isolated from sputum specimens. Bacteriological profiling revealed that 41.26% (n=59) of the isolated bacteria were E. coli, considered as the predominant bacteria isolated from urine specimens. Whereas, S. enterica serover Typhi was the most frequently isolated bacteria from blood specimens accounting for 20.28% (n=29) of all bacteria. Other less prevalent but important pathogenic bacteria included K. pneumoniae accounting for 12.59% (n=18) of all bacteria, P. aeruginosa accounting for 8.39% (n=12) of all bacteria, Acinetobacter spp. accounting for 6.99% (n=10) of all bacteria, and Enterobacter spp. accounting for 2.10% (n=3) of all bacteria. Conclusion. To conclude, the high frequency of GNBs isolated from clinical specimens at Hyderabad, Sindh poses an alarming situation and warrants an urgent need to monitor and control the spread of pathogenic bacteria.